2021
DOI: 10.1177/10547738211061216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Race/ethnicity, Insurance Status, and Area Deprivation on Hip Fracture Outcomes Among Older Adults in the United States

Abstract: This retrospective cohort study used electronic health records to explore the effect of race/ethnicity, insurance status, and area deprivation on post-discharge outcomes in older patients undergoing hip fracture surgery between 2015 and 2018 ( N = 1,150). Inverse probability of treatment weight-adjusted regression analysis was used to identify the effects of the predictors on outcomes. White patients had higher 90- and 365-day readmission risks than Black patients and higher all-period readmissions than the Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(53 reference statements)
1
1
0
Order By: Relevance
“…Specifically, Medicaid and Medicare insurance were associated with decreased odds of both NA and PNB receipt, and uninsured status was associated with decreased odds of NA receipt 19. These results align with previous literature across medical disciplines that have suggested significant socioeconomical and racial differences in healthcare outcomes in breast cancer surgery,31 32 trauma,33 hip fracture surgery,34 and access to genetic counseling in high-risk patients 35…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, Medicaid and Medicare insurance were associated with decreased odds of both NA and PNB receipt, and uninsured status was associated with decreased odds of NA receipt 19. These results align with previous literature across medical disciplines that have suggested significant socioeconomical and racial differences in healthcare outcomes in breast cancer surgery,31 32 trauma,33 hip fracture surgery,34 and access to genetic counseling in high-risk patients 35…”
Section: Discussionsupporting
confidence: 88%
“…Two authors performed the cohort selection independently and discussed and resolved any discrepancies by going through the patients' charts. Further details of cohort selection in this study are shown in Figure 1 and previously reported (Lee et al, 2022).…”
Section: Cohort Selectionmentioning
confidence: 99%